Pendidikan Keluarga sebagai Penentu Kesadaran Penerapan Norma Beragama Siswa - Nasukah, Binti; Shidiq, Ahmad (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2024)
This study examines the role of family education as a determinant of students' awareness in applying religious norms. The research is grounded in previous studies that highlight the significant influence of teacher-led education on students' adherence to religious norms. However, challenges persist in Islamic-based schools, such as SMP Muhammadiyah 5 Pagak, Malang Regency, where some students exhibit low awareness in practicing religious norms despite the school's strong emphasis on religious values. This study aims to confirm whether inadequate family education contributes to these challenges. The research employs a quantitative method with a survey approach. Primary data were collected through questionnaires, while secondary data were gathered through observations and interviews. The findings reveal a positive and significant influence of family education on students' application of religious norms, accounting for 44.9% of the variance. This indicates that higher levels of family education are associated with better adherence to religious norms among students. The study concludes that family education plays a crucial role in shaping students' awareness and application of religious norms. For Islamic educational institutions, addressing students' low awareness in applying religious norms may require collaboration with families to enhance the quality of family education.